Ius Constituendum Urun Dana untuk Badan Usaha Non-Badan Hukum - Muhammad Asrul Maulana; Gabriella Novena Winarta (Prodi Magister Ilmu Hukum Fakultas Hukum Universitas Singaperbangsa Karawang, 2025)
The development of crowdfunding in Indonesia presents legal challenges related to organizer regulations that do not comply with existing provisions, especially for non-legal entities such as social communities, maatschap, or faith-based organizations. Financial Services Authority Regulation No. 57/POJK.04/2020 requires crowdfunding organizers to be established as Indonesian legal entities such as Limited Liability Companies (PT) or cooperatives. However, many crowdfunding practices are carried out by non-formal entities that are not legally recognized, creating a legal vacuum that has the potential to lead to legal uncertainty, misuse of funds, and violations of investor rights. This article proposes the importance of ius constituendum to regulate non-legal entities in crowdfunding activities, with an approach that is more responsive to social and technological dynamics. More flexible regulations are needed to align socio-economic practices with the existing legal system, thereby creating a fair and inclusive legal environment for all forms of crowdfunding activities.